2010
DOI: 10.1007/s11427-010-0102-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogen on diverse stem cells and relevant intracellular mechanisms

Abstract: Sexual dimorphism definitely exists in the pathogenesis of a variety of cardiovascular, neurodegenerative and bone metabolism disorders. Estrogen affects the healing of ischemic myocardium partially through paracrine growth hormone production by bone marrow mesenchymal stem cells (MSCs) and facilitation on mobilization of endothelial progenitors cells (EPCs) to the ischemic myocardium. Estrogen can also inhibit the proliferation of the cardiac fibroblasts. Therefore, estrogen effectively enhances the neovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…There is increasing evidence on the estrogenic aspect of neurogenesis; however, the differential roles of ERα and ERβ in this process still remain to be fully characterized. Considering the currently known role of estrogens in NSC physiology and the regulation of the neurogenesis [124,126,[128][129][130][131][132], the sexual dimorphism we observed in ERα and ERβ expression between male and female NSC [14] supports a sex-based intrinsic difference in the regulation of neurogenesis. In addition, ERα genotype has been recently reported to be responsible for the inter-individual variability of responses to estrogen and testosterone in mesenchymal stem cell-derived osteoblasts [133].…”
Section: Looking At the Forest Instead Of The Tree -Turning The Tide supporting
confidence: 61%
“…There is increasing evidence on the estrogenic aspect of neurogenesis; however, the differential roles of ERα and ERβ in this process still remain to be fully characterized. Considering the currently known role of estrogens in NSC physiology and the regulation of the neurogenesis [124,126,[128][129][130][131][132], the sexual dimorphism we observed in ERα and ERβ expression between male and female NSC [14] supports a sex-based intrinsic difference in the regulation of neurogenesis. In addition, ERα genotype has been recently reported to be responsible for the inter-individual variability of responses to estrogen and testosterone in mesenchymal stem cell-derived osteoblasts [133].…”
Section: Looking At the Forest Instead Of The Tree -Turning The Tide supporting
confidence: 61%
“…The dual or opposite effects of estrogen on cellular proliferation were found not only in vascular SMCs but also in various other cell types [24][25][26][27][28][29]. The mechanisms for this are still unknown but the phenomenon frequently appeared in the cells with different phenotypes (e.g., the mature and un-or de-differentiated) or those isolated M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 10 from individuals with different ages (young and old).…”
Section: Discussionmentioning
confidence: 99%
“…They found that angiogenic factors bFGF, VEGF and SDF‐1α increased in the MSC‐treated hearts compared with medium‐treated hearts, accompanied by increase in capillary density. Some evidence reveals that oestrogen affects the recovery of ischemic myocardium partially through paracrine growth hormone produced by MSCs and facilitation on mobilization of EPCs to the ischemic myocardium, partly via eNOS‐mediated activation of MMP‐9 [54, 55]. It has been shown that MSCs can enhance EC proliferation and sprout formation [56].…”
Section: Paracrine Effectsmentioning
confidence: 99%